KEBERLANJUTAN PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KOTA PEKANBARU (Sustainability of the City Program Without Slums in the City of Pekanbaru) - Islami, Mahardika Era; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Especially by paying attention to the economic, social and environmental concepts. The purpose of this study is to find out how the sustainability of the City without Slums (KOTAKU) program in Pekanbaru City and to determine the inhibiting factors for the sustainability of the City of Slums (KOTAKU) program in Pekanbaru City. This type of research is a qualitative research with a descriptive approach. Data collection obtained both primary and secondary data collected through interviews, observations and documentation and then analyzed so that conclusions can be drawn from the research conducted. The results of this study found that the sustainability of the City without Slums (KOTAKU) program in Pekanbaru City continued in 2019 and continued in 2020.Keywords: Sustainable Development, KOTAKU Program,PartisipationÂ Society